Efficient one-pot construction of unsymmetrical disulfide bonds with TCCA. Issue 3 (18th January 2017) - Yang, Feng; Wang, Wen; Li, Kaidi; Zhao, Weili; Dong, Xiaochun
Graphical abstract: Highlights: A one-pot synthesis of unsymmetrical disulfide with TCCA as oxidant was developed. The reaction was finished within 5 min and wide group tolerance was allowed. Ar-Ar and Ar-alkyl disulfides were synthesized in good to excellent yields. Challenging aliphatic-aliphatic disulfides could also be obtained in good yields. Abstract: We report herein a one-pot synthesis of unsymmetrical disulfides with trichloroisocyanuric acid (TCCA) as an oxidant. Under facile conditions, aromatic-aromatic disulfides and aromatic-aliphatic disulfides were synthesized in good to excellent yields even without base. For the construction of the challenging aliphatic-aliphatic disulfides, good yields of the desired products were also obtained with slightly modified conditions. Additionally, the reactions demonstrated a wide range of substrate scope, very short reaction time (<5 min), and convenient procedures.